The Role of Discourse Analysis in Language Teaching - Ilya Dilmanov; Islam Dilmanov (Researchparks Publishing, 2022)
In this article, a special attention is paid to the main feature of the discourse in language teaching as well as creating suitable contexts for interaction, illustrating exchanges and providing learners with opportunities to process language within a variety of situations are all necessary for developing learning environments.